Assessment of interaction of vanillin with barley, pea and whey proteins: Binding properties and sensory characteristics. (May 2018) - Houde, Marika; Khodaei, Nastaran; Karboune, Salwa
Abstract: Interactions of vanillin with barley proteins (alkaline-based & tri-enzymatic-based barley protein concentrates, AI-BP & TEI-BP) and two control proteins (pea protein concentrate, PPC; whey protein isolate, WPI) were assessed by (a) quantifying the vanillin unbound to the protein at equilibrium, (b) characterizing the structure of protein-vanillin complexes by fluorescence spectrophotometry, and (c) conducting sensory evaluation. Effects of heat- and high-pressure-treatments of proteins on these interactions were also evaluated. The interaction between vanillin and barley proteins, estimated using Klotz plots of unbound vanillin, was found to be non-cooperative, while the quenching of the protein-vanillin complex fluorescence was related to changes in protein binding site hydrophobicity upon vanillin complexation. Using unbound vanillin, native WPI showed the lowest degree of binding, while high-pressure-treated AI-BP concentrate showed the least interaction. Fluorescence spectroscopy analysis revealed the weakest vanillin interaction with heat-treated PPC, followed by heat-treated WPI. The flavor intensity perception results obtained by the sensory evaluation of high protein cookies were well correlated with those predicted by Klotz plots of unbound vanillin., while the consumers' palettes saturation results were comparable to those estimated by the fluorescence spectroscopy. Correlating analytical data with consumers' perception contributes to the understanding of protein/flavor interactions in foods. Highlights: Interaction between vanillin and barley proteins was found to be non-cooperative. Vanillin binding to proteins contributed to tryptophan quenching. Heat and high-pressure treatments greatly reduced protein-flavor interactions. Consumers' intensity scores were well correlated with those estimated from the unbound vanillin. Consumers' palettes saturation levels were comparable to those predicted from quenching of tryptophan fluorescence.